The Christmas jigsaw murders - Benedict, Alexandra, 1977- (Poisoned Pen Press, 2024)
"A puzzling new Christmas mystery from USA Today bestselling author Alexandra Benedict! Rest. In. Pieces. On 1st of December, renowned puzzle setter, loner, and Christmas curmudgeon Edie O'Sullivan finds a hand-delivered present on her doorstep. Unwrapping it, she finds a jigsaw box and, inside, six jigsaw pieces. When fitted together, the pieces show part of a crime scene - blood-spattered black and white tiles and part of an outlined body. Included in the parcel is a message: 'Four, maybe more, people will be dead by midnight on Christmas Eve, unless you can put all the pieces together and stop me.' It's signed, Rest In Pieces. Edie contacts her nephew, DI Sean Brand-O'Sullivan, and together they work to solve the clues. But when a man is found near death with a jigsaw piece in his hand, Sean fears that Edie might be in danger and shuts her out of the investigation. As the body count rises, however, Edie knows that only she has the knowledge to put together the killer's murderous puzzle. Only by fitting all the pieces together will Edie be able to stop a killer - and finally lay her past to rest"--